2021
DOI: 10.3390/antibiotics10111367
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Drug-Resistance-Associated Mutations among Multidrug-Resistant Mycobacterium tuberculosis Isolates in China

Abstract: As the causative bacteria of tuberculosis, Mycobacteriumtuberculosis (M. tb) is aggravated by the emergence of its multidrug-resistant isolates in China. Mutations of six of the most frequently reported resistant genes (rpoB, katG, inhA, embB, gyrA, and rpsL) were detected for rifampicin (RIF), isoniazid (INH), ethambutol (EMB), ofloxacin (OFX), and streptomycin (STR) in this study. The amino acid missense mutations (MMs) and their corresponding single nucleotide polymorphism mutations for all drug-resistant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(30 reference statements)
3
6
4
Order By: Relevance
“…Conversely, the studies of [9,20,21] reported a prevalent mutation of 93.5%, 94.9%, and 91.2% respectively in katG gene which is higher than what was obtained in this study. In this study, the most prevalent rifampin resistance-conferring mutations in rpoB occurred in S531L codon which is comparable with previous studies [9,20,22,23], and could be due to the spread of a prevalent clone. Mutation in this codon is identified as a hot spot for rpoB gene mutations in M. tuberculosis and has been reported in other Provinces of South Africa as well [24] showing that these mutations are prevalent in the country.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Conversely, the studies of [9,20,21] reported a prevalent mutation of 93.5%, 94.9%, and 91.2% respectively in katG gene which is higher than what was obtained in this study. In this study, the most prevalent rifampin resistance-conferring mutations in rpoB occurred in S531L codon which is comparable with previous studies [9,20,22,23], and could be due to the spread of a prevalent clone. Mutation in this codon is identified as a hot spot for rpoB gene mutations in M. tuberculosis and has been reported in other Provinces of South Africa as well [24] showing that these mutations are prevalent in the country.…”
Section: Discussioncontrasting
confidence: 99%
“…This is comparable to the study done by Otchere et al, with a prevalence of 52% [19]. Conversely, the studies of [9,20,21] reported a prevalent mutation of 93.5%, 94.9%, and 91.2% respectively in katG gene which is higher than what was obtained in this study. In this study, the most prevalent rifampin resistance-conferring mutations in rpoB occurred in S531L codon which is comparable with previous studies [9,20,22,23], and could be due to the spread of a prevalent clone.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although resistance to rifampicin and isoniazid is significantly associated with mutations in the Mycobacterium tuberculosis resistance genes rpoB, katG, inhA , and ahpC , these mutations vary in location and frequency in different regions ( 27 , 28 ). For example, the mutation rate at rpoB 531 is as high as 80.9% in Kazakhstan and only 31% in Hungary, and the two mutation patterns of katG 315 and inhA account for a total of 79.9% in Beijing, China ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…INH is the most widely used anti-TB medicine, and INH resistance is more widespread among clinical strains than susceptibility to any other agent [21]. In INH-resistant clinical isolates, mutations in the M. tuberculosis gene are most prevalent, occurring in 50-80% of infections, limiting the catalase-ability peroxidase to trigger the INH pro-drug [22].…”
Section: Isoniazid (Inh) Resistancementioning
confidence: 99%